Hydrogel Design of Experiments Methodology to Optimize Hydrogel for iPSC‐NPC Culture. Issue 4 (5th November 2014) - Lam, Jonathan; Carmichael, S. Thomas; Lowry, William E.; Segura, Tatiana
Abstract : Bioactive signals can be incorporated in hydrogels to direct encapsulated cell behavior. Design of experiments methodology methodically varies the signals systematically to determine the individual and combinatorial effects of each factor on cell activity. Using this approach enables the optimization of three ligands concentrations (RGD, YIGSR, IKVAV) for the survival and differentiation of neural progenitor cells.